2001
DOI: 10.1300/j026v19n01_07
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' Perceptions and Uses of Commercial Drug Information Sources

Abstract: Data were collected from physicians attending a medical conference. This exploratory study was primarily interested in two areas. First, the investigators were interested in better understanding physicians' responses to different promotional tactics typically used by the pharmaceutical industry. Pharmaceutical representatives were most useful, followed by drug samples and infomercials in medical journals. Direct mail, promotional faxes, and promotional products were used less by physicians. Second, the investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 7 publications
0
27
0
Order By: Relevance
“…PR visits are part of a well-organized pharmaceutical marketing plan. 8,[56][57][58][59] Our findings suggest that policies that restrict or eliminate access, or clearly define the parameters of interactions may allow prescribers to maintain social norms and limit PR influence. Such interventions should be studied.…”
Section: Social Contractsmentioning
confidence: 80%
“…PR visits are part of a well-organized pharmaceutical marketing plan. 8,[56][57][58][59] Our findings suggest that policies that restrict or eliminate access, or clearly define the parameters of interactions may allow prescribers to maintain social norms and limit PR influence. Such interventions should be studied.…”
Section: Social Contractsmentioning
confidence: 80%
“…For example, David W (2000)reported that detailing from pharmaceutical sales representatives could lead physicians to ask management to add the detailed drugs to the "hospital formulary points. ".Many researchers in fact believe that pharmaceutical sales representatives have a strong persuasive effect (Spiller and Wymer Jr (2001);Narayanan et al, 2003). What's more, the intensity of pharmaceutical detailing impacts drug prescription rates.…”
Section: Factors That Affect Physicians' Drug Selectionmentioning
confidence: 99%
“…1 The remaining 2%enearly $400 millionewas spent on advertising in medical journals. 1 There is evidence that physician-targeted advertising of prescription medicines influences prescribing behavior [2][3][4] in ways that physicians themselves may 4 or may not 3 appreciate. One study suggests that journal advertising can achieve rate of message penetrationedefined as an alteration in prescribing intention of a physicianeof up to 64% for unique products and 42% for products with in-class competitors.…”
mentioning
confidence: 99%